Confidence: How to Overcome Self-Doubt, Insecurity, and Fears. - Guttormsen, TJ (linkedin.com, 2021)
One of the biggest blockers to professional success can be a lack of self-confidence. This course includes information and practical exercises to help you improve social confidence.